Some remarks on Ricoeur's Hermeneutics - Garnica, Antonio Vicente Marafioti (1993)
This paper presents remarks on the basis of Ricoeur's Hermeneutics Phenomenology. To achieve this, it begins by examining aspects of Heidegger's Phenomenology and focusing on aspects of the distinction between Structural and Hermeneutic Phenomenologies, that is, on Heidegger's and Ricoeur's conceptions of Hermeneutics founded in Phenomenology.